2022
DOI: 10.1021/acscatal.2c02617
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Sulfur Dissolution and Enhancing Activity of SnS for CO2 Electroreduction via Electronic State Modulation

Abstract: Heteroatom doping can facilitate intrinsic activity via the tuning of electronic states. However, it is still rare to elucidate the role of a specific metal sulfide electronic state and simultaneously enhance the CO2 electroreduction reaction (CO2RR) stability. SnS is well-known for its ability to produce HCOOH; however, its long-term operational stability is limited by sulfur dissolution. Herein, we propose a strategy to reinforce the S atoms via heteroatom (In) doping. In situ Raman tests and theoretical cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Benefiting from the outstanding initial activity and selectivity, the low-melting-point metals (e.g., Pb, Bi, Sn, Cd, In, etc.) are considered to be the state-of-the-art electrocatalysts for selective CO 2 to HCOOH. Specifically, the high overpotential for the hydrogen evolution reaction (HER) on low-melting-point metals enables the production of HCOOH with acceptable selectivity in commonly used aqueous electrolytes . Meanwhile, benefiting from the preferred affinity for intermediates in the HCOOH pathway, high coverage of the target intermediate allows HCOOH to be produced with reasonable selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the outstanding initial activity and selectivity, the low-melting-point metals (e.g., Pb, Bi, Sn, Cd, In, etc.) are considered to be the state-of-the-art electrocatalysts for selective CO 2 to HCOOH. Specifically, the high overpotential for the hydrogen evolution reaction (HER) on low-melting-point metals enables the production of HCOOH with acceptable selectivity in commonly used aqueous electrolytes . Meanwhile, benefiting from the preferred affinity for intermediates in the HCOOH pathway, high coverage of the target intermediate allows HCOOH to be produced with reasonable selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…The integration of the crystal orbital Hamilton population (ICOHP) was further performed to investigate the coupling of Cu 3d–O 2p and Ce 4+ 4f–O 2p in Ce-Cu 2 O and Cu 2 O (Figures C–E). The ICOHP value for the Ce 4+ 4f–O 2p bond in Ce-Cu 2 O (−4.037) (Figure C) exceeded that for the Cu (3d)–O (2p) bond in both Ce-Cu 2 O (−1.743) and pure Cu 2 O (−1.492) (Figures D and E), signifying the crucial role of the unconventional orbital hybridization between the high-order Ce 4+ 4f and O 2p in preventing lattice oxygen leaching and stabilizing Cu + during the reduction process again, compared with the traditional d–p interaction . In addition, the larger ICOHP value for the Cu (3d)–O (2p) bond in Ce-Cu 2 O (−1.743) compared to pure Cu 2 O (−1.492) substantiated the enhanced stability of the Cu–O bond in Ce-Cu 2 O compared to that in pure Cu 2 O (Figures D and E).…”
Section: Resultsmentioning
confidence: 94%
“…The EIS results further demonstrated that under‐coordinated Bi active sites and surface chemical microenvironment modulation by DETA functionalization could boost the charge‐transfer rate of mBi‐DETA NSs from the cathode surface to CO 2 * species led to accelerate the RDS. [ 48 ] The electrochemically active surface area (ECSA) represents the number of active sites, which is proportional to the capacitance ( C ) value of the electrode. So, ECSA of the catalyst was determined using the double layer capacitance ( C dl ) method to further investigate the intrinsic activity of the catalyst.…”
Section: Resultsmentioning
confidence: 99%